2018
DOI: 10.2134/jeq2017.04.0161
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Soil Organic Carbon Responses to Crop Rotation, Tillage, and Climate Change in North Dakota

Abstract: Understanding how agricultural management and climate change affect soil organic carbon (SOC) stocks is particularly important for dryland agriculture regions that have been losing SOC over time due to fallow and tillage practices, and it can lead to development of agricultural practice(s) that reduce the impact of climate change on crop production. The objectives of this study were: (i) to simulate SOC dynamics in the top 30 cm of soil during a 20-yr (1993-2012) field study using CQESTR, a process-based C mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Mukherjee and Lal (2014) found that "carbon dioxide emissions from biochar-amended soils have been enhanced up to 61% compared with It is essential to realistically examine the effects of CSA management practices on SOC and greenhouse gases at multiple scales from plot and field levels to regional and global scales. For example, modeling studies have attempted to investigate regional cropland SOC dynamics as influenced by multiple global environmental changes while considering more traditional and less CSA practices (e.g., Molina, Moreno Pérez, & Pérez, 2017;Nash et al, 2018;Ren, Tian, Tao, Huang, & Pan, 2012. For example, modeling studies have attempted to investigate regional cropland SOC dynamics as influenced by multiple global environmental changes while considering more traditional and less CSA practices (e.g., Molina, Moreno Pérez, & Pérez, 2017;Nash et al, 2018;Ren, Tian, Tao, Huang, & Pan, 2012.…”
Section: Uncertainty Analysis and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mukherjee and Lal (2014) found that "carbon dioxide emissions from biochar-amended soils have been enhanced up to 61% compared with It is essential to realistically examine the effects of CSA management practices on SOC and greenhouse gases at multiple scales from plot and field levels to regional and global scales. For example, modeling studies have attempted to investigate regional cropland SOC dynamics as influenced by multiple global environmental changes while considering more traditional and less CSA practices (e.g., Molina, Moreno Pérez, & Pérez, 2017;Nash et al, 2018;Ren, Tian, Tao, Huang, & Pan, 2012. For example, modeling studies have attempted to investigate regional cropland SOC dynamics as influenced by multiple global environmental changes while considering more traditional and less CSA practices (e.g., Molina, Moreno Pérez, & Pérez, 2017;Nash et al, 2018;Ren, Tian, Tao, Huang, & Pan, 2012.…”
Section: Uncertainty Analysis and Prospectsmentioning
confidence: 99%
“…Therefore, future CSA research is expected to include varied climate and geographic conditions, address more biogeochemical and hydrological processes, and apply diverse methods such as the data-model fusion approach. For example, modeling studies have attempted to investigate regional cropland SOC dynamics as influenced by multiple global environmental changes while considering more traditional and less CSA practices (e.g., Molina, Moreno Pérez, & Pérez, 2017;Nash et al, 2018;Ren, Tian, Tao, Huang, & Pan, 2012.…”
Section: Uncertainty Analysis and Prospectsmentioning
confidence: 99%
“…Nash et al (2018a) simulated SOC dynamics in the top 30 cm in a 20‐yr field study using a process‐based C model, CQESTR, to predict the impact of changes in management, crop production, and climate change, and to identify the best dryland cropping systems to maintain or increase SOC stocks under projected climate change in central North Dakota. Intensifying crop rotations was predicted to have a greater impact on SOC stocks than minimum tillage or NT.…”
Section: Process‐based Models To Evaluate Soil Organic Carbon Dynamicsmentioning
confidence: 99%
“…CQESTR predictions indicated that soil C saturation may be reached in high-residue rotations, and that increasing SOC deeper in the soil profile will be required for long-term SOC accretion beyond 2030 as long as conservation tillage and cover crops together with high-residueproducing corn are used in these loamy sand soils. Nash et al (2018a) simulated SOC dynamics in the top 30 cm in a 20-yr field study using a process-based C model, CQESTR, to predict the impact of changes in management, crop production, and climate change, and to identify the best dryland cropping systems to maintain or increase SOC stocks under projected climate change in central North Dakota. Intensifying crop rotations was predicted to have a greater impact on SOC stocks than minimum tillage or NT.…”
Section: Process-based Models To Evaluate Soil Organic Carbon Dynamicsmentioning
confidence: 99%
“…In this system, a fallow period ranging from 14 to 21 mo was maintained to allow soil water recharge (Black & Power, 1965; Black, Siddoway, & Brown, 1974; Hansen et al., 2012; Merrill et al., 1999; Nielsen & Calderon, 2011; Peterson, Schlegel, Tanaka, & Jones, 1996), mineralization of organic N (Haas, Evans, & Miles, 1957; Haas, Willis, & Bond, 1974; Michalyna & Hedlin, 1961), and chemical or mechanical weed control (Derksen, Thomas, Lafond, Loepply, & Swantson, 1994; Fenster & Wicks, 1982; Lenssen, Johnson, & Carlson, 2007; Lyon, Miller, & Wicks, 1996; Peairs, Bean, & Gossen, 2005) between wheat crop phases. The use of this system contributed to the Dust Bowl that occurred during the 1930s, and was responsible for excessive soil erosion (Farney, Bullock, McGinn, & Fryer, 1995; Farney, Lindwall, Izaurralde, & Moulin, 1994; Lafond et al., 1993), reductions in soil organic matter (SOM) (Campbell et al., 2005; Cochran, Danielson, Kolberg, & Miller, 2006; Haas, Evans, & Miles, 1957; Monreal, Zentner, & Robertson, 1997; Nash et al., 2018), saline seep formation (Black, Brown, Halvorson, & Siddoway, 1981; Halvorson & Black, 1974; Willis, Bauer, & Black, 1983), and economic inefficiencies (Aase and Schaefer, 1996; Dhuyvetter, Thompson, Norwood, & Halvorson, 1996; Halvorson, Anderson, Toman, & Welsh, 1994). Extended fallow also negatively impacted soil health (Acosta‐Martinez, Mikha, & Vigil, 2007; Doran, Elliott, & Paustian, 1998; Lupwayi, Rice, & Clayton, 1999; Nielsen & Calderón, 2011; Steenwerth, Jackson, Calderón, Stromberg, & Scow, 2002; Wienhold et al., 2006; Wright & Anderson, 2000).…”
Section: Introductionmentioning
confidence: 99%